Peran Tim PPK Ormawa BEM FK UPR dalam Peningkatan Pengetahuan Anemia dan Skrining Kadar Hemoglobin Remaja Putri MTS dan MA Darul Ulum, Palangka Raya - Novita Wulandari; Sazly, Muhammad Revo Andaluzio; Ananda, Desire Reskia; Prasetyo, Dafiq Amral; Daniel Yuantara; Darsana, I Nyoman; Adinda, Naya Safira; Murti, Tabita Hayu Panca; Vany, Destia; Anna; Sihombing, Katrin; Budi Aulyansyah Ahmad Trisna; A.Irwin Putra Pangestin; Ni Nyoman Sri Yuliani (Jurnal Pengabdian Kampus, 2024)
Stunting is a malnutrition condition in toddlers who have less height compared to children their age, and anemia is one of the main causes. Adolescent girls who experience anemia are at high risk of developing it until pregnancy, negatively impacting fetal development and causing Low Birth Weight (BBLR) or prematurity. The "SIRTUIN" Community Empowerment Program by PPK ORMAWA BEM FK UPR aims to reduce stunting in Pahandut Village, Palangka Raya City, which has a high stunting rate. One of the programs, ARTERI, focuses on adolescent girls in MTs and MA Darul Ulum to prevent anemia. This activity includes counseling, hemoglobin (Hb) screening, and pre and post tests to measure student knowledge. Of the 62 participants, 11 students were diagnosed with anemia with an average Hb level of 13.37 g/dl. Counseling increased anemia awareness from an average score of 65.48 to 84.84. The results showed a significant increase in awareness and knowledge about anemia after the activity, signaling the effectiveness of the program. The activity succeeded in raising awareness and health of adolescent girls related to anemia, with the hope of preventing stunting in the future.